Enhanced RNA replication and pathogenesis in recent SARS-CoV-2 variants harboring the L260F mutation in NSP6. - Taha Y Taha; Shahrzad Ezzatpour; Jennifer M Hayashi; Chengjin Ye; Francisco J Zapatero-Belinchón; Julia A Rosecrans; Gabriella R Kimmerly; Irene P Chen; Keith Walcott; Anna Kurianowicz; Danielle M Jorgens; Natalie R Chaplin; et al. (PLoS Pathogens)
The COVID-19 pandemic has been driven by SARS-CoV-2 variants with enhanced transmission and immune escape. Apart from extensive evolution in the Spike protein, non-Spike mutations are accumulating across the entire viral genome and their functional impact is not well understood. To address the contribution of these mutations, we reconstructed genomes of recent Omicron variants with disabled Spike expression (replicons) to systematically compare their RNA replication capabilities independently from Spike. We also used a single reference replicon and complemented it with various Omicron variant Spike proteins to quantify viral entry capabilities in single-round infection assays. Viral entry and RNA replication were negatively correlated, suggesting that as variants evolve reduced entry functions under growing immune pressure on Spike, RNA replication increases as a compensatory mechanism. We identified multiple mutations across the viral genome that enhanced viral RNA replication. NSP6 emerged as a hotspot with a distinct L260F mutation independently arising in the BQ.1.1 and XBB.1.16 variants. Using mutant and revertant NSP6 viral clones, the L260F mutation was validated to enhance viral replication in cells and increase pathogenesis in mice. Notably, this mutation reduced host lipid droplet content by NSP6. Collectively, a systematic analysis of RNA replication of recent Omicron variants defined NSP6's key role in viral RNA replication that provides insight into evolutionary trajectories of recent variants with possible therapeutic implications.